Accounting Control and Organizational Performance: An Investigation of Achievement Motivation in Higher Education Institutions - Karlina Ghazalah Rahman; Anita Achmad Payu (Ilomata International Journal of Tax and Accounting, 2026)
This study evaluates the contribution of Internal Control Systems (ICS) and achievement motivation toward institutional performance in Private Higher Education Institutions (PTS) in Makassar. This issue is highly relevant given the managerial compliance challenges and accreditation risks facing private universities. The novelty of this research lies in examining whether Need for Achievement (n-Ach) moderates the relationship between Internal Control Systems (ICS) and institutional performance, bridging the gap between psychological drivers and formal controls. Using a causal-explanatory quantitative approach, data were collected from 78 strategic managers and senior lecturers across five accredited private universities and analyzed via Structural Equation Modeling (SEM-PLS). Empirical findings demonstrate that both ICS and n-Ach independently exert positive and significant effects on university performance (p < 0.05). However, the interaction between these variables was not significant, indicating that n-Ach does not serve as a moderator. These results suggest that performance is currently driven by individual control mechanisms and personal motivation rather than their synergistic interaction. The study highlights the importance of harmonizing accountable control mechanisms with the creative autonomy desired by achievement-oriented individuals to prevent bureaucratic barriers to innovation.